Personal and institutional barriers, as the basis of the glass ceiling in the promotion of women in organizations - Ali Poorbehroozan; Ali hamidizadeh; Raza Seraji (فصلنامه زن و جامعه, 2021)
So far, there has been a great deal of research into the characteristics of the organizations in which the glass ceiling has been created and the processes that govern them. But less has been noted that Hofstede's interpretation of organizational culture is influenced by the culture of society. Thus, other dimensions outside the organization are complementary to organizational inhibitors. The purpose of this study was to identify complementary organizational inhibitors in promoting women to managerial positions. The research method is based on interpretive paradigm, inductive approach and qualitative method. Research data were also obtained through interviewing tools. Content analysis was used to analyze the data. The statistical population of the study consisted of employees and managers of Tehran municipality with 19 persons including 14 women and 5 men. Findings showed that barriers to women's participation and participation were not only organizational factors, but also personal and Institutional barriers. Organizational barriers include barriers to formal and informal space. Personal barriers include family factors, women's attitudes and skills, and Institutional barriers include government performance and the role of public culture in society.